Nanoporous sheets and cylinders via bulk templating of triblock terpolymer/homopolymer blends - Betthausen, Eva; Dulle, Martin; Hanske, Christoph; Mueller, Melanie; Fery, Andreas; Foerster, Stephan; Schacher, Felix H.; Mueller, Axel H. E. (Macromolecules, 2014)
The selective cross-linking of individual domains in block copolymer bulk morphologies represents an elegant strategy to generate nanostructured materials of tunable size and geometry. We demonstrate the preparation of highly periodic nanoporous sheets and core-shell cylinders from a stimuli-responsive triblock terpolymer, polybutadiene-block-poly(tert-butyl methacrylate)-block-poly(2-(dimethyl-amino)ethyl methacrylate) (PB-b-PtBMA-b-PDMAEMA). By blending the terpolymer with different types and amounts of homopolymers, a variety of bulk morphologies is accessible, including rarely found examples such as tetragonally perforated lamellae and double gyroid networks. Selective cross-linking of the PB domains of the generated morphologies followed by sonication-assisted dispersion allows the preparation of well-defined nanostructures in nonselective solvents. Because of the PDMAEMA corona, the cross-linked structures are soluble in aqueous media. The high regularity of the pore diameter in combination with a tunable pore permeability by two external stimuli, pH and temperature, renders such perforated lamellae particularly appealing for potential applications as membrane materials.
CRIS-Team Scopus Importer:2023-03-20